The Fathomless Ocean of Objectivity, Death, and Memory: An OOO reading of the Solaris Ocean in Stanislaw Lem’s Solaris - Tembo, Kwasu (Imagining the Impossible: International Journal for the Fantastic in Contemporary Media, 2024)
Stanislaw Lem’s 1961 sci-fi classic Solaris features one of the most enduring, strange, and seemingly inexhaustible presentments of the concept of an ocean. Lem’s economy of craft resonantly renders the premise of the text on the idea that there are inescapable ontological gaps between objects encountering one another. Using immense detail, and a scientific, specifically historiographic, naturalist, and philosophical style of prose, Lem frames this idea as the complete failure of human beings to understand an extraterrestrial intelligence. The narrative follows a team of terrestrial scientists as they attempt to probe, examine, and communicate with the oceanic surface of the planet Solaris from a research station hovering above it. Based on years of research and study, the Solarists deduce that the planet, through its oceanic membrane, can somehow manifest the ability to (re)produce human secrets and guilt into material form. That form, which physically appears on the station and confronts its crew, is dependent on the specific consciousnesses of each scientist aboard. The research of the Solarists also reveals that any human attempt to formalize and concretize the phenomenological occurrences of the ocean that ’make sense’ always fail. For Lem, “[t]he peculiarity of those phenomena seems to suggest that we observe a kind of rational activity, but the meaning of this seemingly rational activity of the Solarian ocean is beyond the reach of human beings” (Lem 1989). As a type of ’memory-machine’, Lem’s ocean seems to act as some kind of psycho-emotional repository in which and from which various psycho-emotional affects are repressed, restored, and reproduced. Because of the radical indeterminacy of human understandings of the ocean, it is difficult if not impossible to say “why” the Solaris ocean does what it does, to attribute to its processes anything intentional, or to ascribe any anthropocentric teleology or technology to its phenomena and processes. While critics have applied numerous, and typically psychoanalytically-informed readings of the Solaris ocean, such a move subjectivizes the ocean at the expense of the seemingly inexhaustible and interesting aspects of its objectivity (its status as an object). An object oriented approach allows us to better tease these out, and open up the depths of alienness and familiarity that, while ostensibly akin to the psycho-emotional trenches of the human unconscious, are externalized in the form of a truly strange object which in turn (re)produces truly strange objects. In view of the above, this paper seeks to accomplish the following: 1) to assert that an object oriented approach will offer better footing from which to prosecute any reading concerning the Solaris ocean’s relationship with trauma and opportunity, (re)exposure, and healing; 2) offer a Post-romantic, object oriented analysis of Lem’s well-crafted, detailed representation of radical alienness through the paradoxically concrete, albeit also radically indeterminate, image of an ocean-like entity/superstructure/hyperobject/space; 3) explore the encounters between the oceanic space with both human actors and the technology that mediates said interaction.